Throughput enhancement of car exhaust fabrication line by applying MOST - Hanash, Ebrahim; Karim, A.N. Mustafizul; Tuan, SaravananTanjong; Mohiuddin, A. K. M. (IOP Publishing, 2017)
In the fiercely competitive world market of today, manufacturers are facing increasingly tougher challenges and are compelled to find ways for productivity enhancement wherever possible in the whole supply chain. Nevertheless there are many facets in business process which can be explored for possible improvement, an immediate focus goes for the involved processes to re-engineer the activities in different workstations for an efficient and balanced assembly or fabrication line. In this paper an industrial case on fabrication line of a car exhaust system is presented to illustrate the scope of improvement by applying the MOST (Maynard’s Operation Sequence Technique) in streamlining the activities followed by assembly line balancing (ALB). The whole process of conducting various tasks is investigated to find out the lapses or wastes, to search for better option and to set the standard times for the tasks. Then individual workstation time is worked out by summing up the standard times of the involved tasks or activities and the concept of ALB is attempted to balance the fabrication line. So by possible reduction or elimination of the identified wastes or lapses workstation times including the bottleneck station are lowered. As a result the throughput of car exhaust systems is enhanced. According to the current practice, the Takt time is set at 3 minutes. However, upon an analysis through use of the MOST, the bottleneck station time is found to be as low as 1.27 minutes. Thus an opportunity of meeting the current level of demand with significantly lower workforce (with 2 operators instead of 5) is revealed. Alternatively, if necessary, an increased workload can be assigned for the current level of workforce. Moreover, with proper distribution of activities among the workstations using the concept of ALB, the line efficiency is found to be improved. So the line balance loss in the current setup of production line is also possible to be largely reduced. Thus daily production of car exhaust, if modified with suggested changes with the current workforce, could be more than double compared to the current daily output. Hence, effectiveness of the MOST followed by ALB applications to expose and remove the operational wastes in the work flow is reiterated with enhanced throughput.